SINTESIS DAN AKTIVITAS ANTIOKSIDAN 3-(3,4-dimetoksifenil)-1-(4-metilfenil)-2-propen-1-on - Dian Agung Pangaribowo; Indah Purnama Sary; Dwi Koko Pratoko (Fakultas Kedokteran Gigi Universitas Jember, 2014)
A new compound from chalcone derivate has been synthesized from 4-methylacetophenone and 3,4-dimethoxybenzaldehyde by Claisen-Schmidt condensation with catalyst of NaOH 60%. This compound is 3-(3,4-dimethoxyphenyl)-1-(4-methylphenyl)-2-propen-1-one. Structureelucidation was conducted by FTIR and 1H-NMR analysis. The compound is relatively pure and this can be identified by only one spot on TLC analysis and the range of melting point is narrow. Antioxidant activity evaluation of the compound with DPPH method showed that IC50 is 455.312 ppm, lower than vitamin C as the standard.